Poetic machinations : allegory, surrealism, and postmodern poetic form - Golston, Michael (Columbia University Press, 2015)
The shape, lineation, and prosody of postmodern poems are extravagantly inventive, imbuing their form with as much meaning as their content. Through a survey of American poetry and poetics from the end of World War II to the present, Michael Golston traces the proliferation of these experiments to a growing fascination with allegory in philosophy, linguistics, critical theory, and aesthetics, introducing new strategies for reading American poetry while embedding its formal innovations within the history of intellectual thought. Beginning with Walter Benjamin's explicit understanding of Surrea.